Approximation of classes of Poisson integrals by Fejer means - O. Rovenska (Математичні Студії, 2023)
The paper is devoted to the investigation of problem of approximation of continuous periodic functions by trigonometric polynomials, which are generated by linear methods of summation of Fourier series.